The impact of COVID-19 on students’ anxiety and its clarification: a systematic review - Wu, Jiarun; Kuan, Garry; Lou, Hu; Hu, Xiaoyu; Masri, Mohamad Najmi; Sabo, Abdulwali; Kueh, Yee Cheng (Frontiers in Psychology, 2023)
Introduction: Since the emergence of COVID-19 in 2019, every country in the world has been affected to varying degrees. Long-term psychological pressure and anxiety will inevitably damage students' physical and mental health. This study aimed to examine the Impacts and elucidation among students with stress and anxiety during the COVID-19 pandemic and discuss which intervention was best the best intervention.Methods: A comprehensive literature search was conducted between January 2020 to December 2022, using online databases such as PubMed, Web of Science, Scopus, and Google Scholar by using the following keywords in combination: "COVID-19", "stress," "anxiety," "depression" and "intervention." The retrieved literature was screened and examined.Results: A total of 2924 articles were retrieved by searching subject words and keywords. After screening through the titles and abstracts, eighteen related studies were retained. A review of these 18 articles found that: (1) most studies did not use medication to control stress and anxiety; (2) The standard methods used to reduce stress and anxiety were religion, psychological counseling, learning more about COVID-19 through the media, online mindfulness courses, improving sleep quality, and physical exercise; (3) The most effective interventions were physical activity and raising awareness about COVID-19 through media and mindfulness online programs. However, some studies show that physical activity cannot relieve psychological stress and anxiety directly. Conclusion: Limited interventions have been shown to be are effective but learning more about COVID-19 and using active coping strategies can help reduce stress and anxiety. The implications of the COVID-19 were discussed.